Additional vitamin D supplementation does not affect muscle strength in the older women: A double-blind randomized controlled trial - Nurahmatika, Prisma; Noer, Etika Ratna; Ngestiningsih, Dwi; Susanto, Hardhono; Pramono, Adriyan; Supatmo, Yuswo (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2024)
Background: The elderly, aged 60 and above, are expected to increase in number in the coming years. Aging brings about various changes, impacting both physical and mental health. Proper protein intake and exercise can boost muscle protein synthesis, while maintaining optimal vitamin D levels is crucial. Research is necessary to explore vitamin D's impact on elderly muscle mass.Objective: This study aims to investigate the effect of adding vitamin d supplementation to protein and exercise on handgrip strength in healthy elderly.Materials and Methods: 24 participants were randomized in a double-blinded, pilot study ages 60- 80 years Subjects were divided into two groups. Group 1 was given interventions of vitamin D supplementation 1000 UI/day combining soy + oats milk as a protein and exercise. The second group was given intervention of soy+ oats milk protein, and exercise. The intervention program was administered for 8 weeks. Data comparison whitin and between groups were analyzed by Independent T-test, Mann-Whitney, and Paired T-testResults: Data from all participants was analyzed, before and after interventions of handgrip was increased in both of groups from a mean of 17.18kg to 18.06kg for the right hand and 15.17kg to 18.26kg for the left hand in Group 1, 13.80kg to 16.86kg for the right hand and 15.45kg to 17.32kg for the left hand in Group 2. Results of the difference test analysis between the two groups (ANOVA t = 0.548, P= 0172) showed no difference between group 1 and group 2.Conclusion: In this study, there was no effect of adding vitamin D supplementation on handgrip at healthy elderly participants.